Placing blame : a general theory of the criminal law / Michael Moore. - Moore, Michael S., 1943- (Oxford University Press, 2010)
With this volume, Michael Moore offers the first thorough examination of the retributivist theory of the criminal law. He not only defends the theory, but also details the implications it would have for the general structure of criminal law.